Pengaruh Komite Audit,Financial Distress, Komisaris Independen Terhadap Audit Delay (Studi Empiris Pada Perusahaan Indeks LQ45 Di Bursa Efek Indonesia) - Sabrina Nabilah Putri; Rananda Saptanta (CV. ITTC INDONESIA, 2026)
This study aims to analyze and provide empirical evidence of the effect of the audit committee, financial distress, and independent commissioners on audit delay in companies included in the LQ45 Index listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This study employs a quantitative method using a multiple linear regression approach. The sample was selected using a purposive sampling technique, resulting in 18 companies that met the criteria during the observation period, with a total of 108 observations. The data used are secondary data in the form of annual financial statements published by the companies. The results indicate that simultaneously, the audit committee, financial distress, and independent commissioners have an effect on audit delay. Partially, the audit committee and financial distress have an effect on audit delay, while independent commissioners do not have an effect on audit delay.